Effect of Taichi Exercise on Blood Pressure in a Family with Hypertension in Banjarsengon Village: A Case Study - Amalia, Syifa; Kurdi, Fahruddin (Journal of Rural Community Nursing Practice, 2024)
Hypertension is a critical global health issue that affects quality of life and increases the risk of cardiovascular disease. The purpose of this case study is to assess the efficacy of Taichi exercise as a nonpharmacological therapy for decreasing blood pressure in the family with hypertension. Mrs. H, a 49-year-old single mother with a history of hypertension lived in Banjarsengon Village, Jember. The Taichi exercise intervention was performed twice a week for three weeks. Following six sessions of Taichi exercise, total systolic blood pressure decreased by 10 mmHg and diastolic by 6 mmHg. Family empowerment through the participation of Mrs. H's children in supporting the implementation of Taichi exercise is key in this therapeutic approach. The results of this study suggest that Taichi exercise has potential as a safe and effective alternative therapy for the management of hypertension. In order for the hypertension management program in families to have maximum impact, it is very necessary to increase family empowerment through health workers in community health centers who are monitored periodically.